Thermo-physical properties of TiO2-SiO2 hybrid nanofluids dispersion with water/bio-glycol mixture - Zainon, S. N. M.; Azmi, W. H.; Hamisa, A. H. (IOP Publishing, 2021)
Introducing nanoparticles in liquid-based mixtures began to gain attention in various industries. This is supported by previous studies to improve the performance and provide energy saving for the system. Among its uses is in the VCRS and automotive air conditioning (AAC) system. The lubricant used in this system has the potential to have a good effect on the performance. Before testing the nano-lubricant enhancement performance, an automotive air conditioning (AAC) system test rig based on hybrid electric vehicles (HEV) AC system has to be developed; therefore, this paper presented the development process of AAC test rig specific for the HEV. In order to analyze the performance, 11 thermocouples, digital pressure gauges with the data logger, and AC/DC power clamp were assembled and used. After that, the experiment was conducted with five different initial refrigerant charges and three different compressor speeds. This method was applied to both pure POE lubricant and SiO2/POE nano-lubricant. Then, the heat absorbs, compressor work, and coefficient of performance (COP) were evaluated. The highest average COP for SiO2/POE nano-lubricant was achieved at a 40 % duty cycle (2520 RPM) speed with a value of 2.84. The highest enhancement of the COP is 25.1% at 60% duty cycle (3180 RPM) speed with 160 grams of initial refrigerant charged an average enhancement of the COP is 13.16%.